2008
DOI: 10.1021/ol800063d
|View full text |Cite
|
Sign up to set email alerts
|

Direct Construction of Bicyclic Heterocycles by Palladium-Catalyzed Domino Cyclization of Propargyl Bromides

Abstract: The palladium-catalyzed domino cyclization of propargyl bromides having two nucleophilic functional groups is described. Treatment of 1,7-diamino-5-bromohept-3-yne derivatives with catalytic Pd(PPh3)4 in the presence of NaH in MeOH gives the 2,7-diazabicyclo[4.3.0]non-5-enes in good yields. Interestingly, the regioselectivity of the reaction is completely controlled by the relative reactivity of the amine functional groups, irrespective of the position of the nucleophiles. The malonate derivative also undergoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Ohno has imaginatively constructed bicyclic heterocycles by palladium catalyzed domino cyclization of propargyl bromides 15. Yoshida has devised a clever palladium catalyzed three component coupling of propargylic oxiranes, phenols, and carbon dioxide 16.…”
Section: Introductionmentioning
confidence: 99%
“…Ohno has imaginatively constructed bicyclic heterocycles by palladium catalyzed domino cyclization of propargyl bromides 15. Yoshida has devised a clever palladium catalyzed three component coupling of propargylic oxiranes, phenols, and carbon dioxide 16.…”
Section: Introductionmentioning
confidence: 99%
“…[6] More recently, Ohno et al reported the first Pd-catalyzed intramolecular Heck-type reaction of oxime ethers with an aryl halide moiety to give indolin-3one O-alkyl oximes. [7,8] Good stereoselectivity (up to > 98:2 Z selectivity) was observed for the reaction irrespective of the isomeric ratio of the starting material. In 2008, Cheng et al reported the annulations between aromatic aldoxime ethers and aryl iodides through Pd-catalyzed C À H activation and subsequent intramolecular oxidative Heck cyclization.…”
Section: Introductionmentioning
confidence: 92%
“…100 Ohno et al reported that the palladium-catalyzed domino cyclizations of propargyl bromides 130, possessing two nucleophilic functional groups, with catalytic tetrakis(triphenylphosphine)palladium(0) in the presence of sodium hydride in methanol gave 2,7-diazabicyclo[4.3.0]non-5-enes 132 in good yields (Scheme 43). 101 The regioselectivity of the reaction was entirely controlled by the relative reactivity of the amine functional groups, irrespective of the position of the nucleophiles. Lautens and co-workers reported 102 a one-pot procedure combining the copper-catalyzed Huisgen cycloadditions of alkynes and azides (CuAAC) 103 and palladium-catalyzed direct annulation by C-H bond activation 104 for the synthesis of structurally unique polycyclic frameworks 134 in good to excellent yields (62-97%) from different heterocycle-substituted aryliodoacetylenes 133.…”
Section: Scheme 40mentioning
confidence: 99%